The Rule of Law and Economic Growth in the Balkan States - Michaela Ftoreková; Michal Mádr (European Journal of Business Science and Technology, 2017)
The main aim of the paper is to evaluate whether the rule of law affects economic growth in the Balkan states. The reference period is the period 2000-2015 due to data availability. As indicators of the legal environment the Rule of Law Index (the Worldwide Governance Indicators) and Property Rights Index (the Index of Economic Freedom) are employed. The paper uses panel data regression analysis (OLS with fixed effects) for the purpose of identification and quantification. The results indicate that improvement of the rule of law has not statistically significant effect on growth in the Balkan countries. On the other hand, the higher level of property rights might support economic development in the countries, but simultaneously the positive changes prove to be in five-year horizon.